PENINGKATAN HASIL BELAJAR LARI ESTAFET DENGAN MENGGUNAKAN MODIFIKASI PERMAINAN PIENJONG PADA SISWA KELAS 6 SDN 1 KEMIRIOMBO KECAMATAN GEMAWANG KABUPATEN TEMANGGUNG (Department of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this research is to improve learning outcomes relay with modifications pienjong game on the Grade 6 students at SDN 1 Kemiriombo, District Gemawang, Regency Temanggung. This study uses action research implementation consists of two cycles. Each held one meeting cycle consists of four stages, namely: planning, implementation, observation, and reflection. The instrument used in this study is the test performance of students, student observation sheet, and a written test. Based on the results, the percentage of mastery learning outcomes in cycle 1, psychomotor aspects of 43.7%, 93.7% affective aspects, cognitive aspects of 18.7%, and mastery learning students is 62.5% of the total number of students. In cycle 2 psychomotor aspects of 93.7%, 100% affective aspects, cognitive aspects of 43.7%, and mastery learning students is 81.3% of the total number of students. Present study showed an increase in mastery learning students by 18.8%, from 62.5% in Cycle 1 to 81.3% in cycle 2. Based on the above results, it was concluded that the modification of the game pienjong relay in learning can improve learning outcomes of students grade 6 SDN 1 Kemiriombo.